Family Systems and Cultural Adaptation in Psychosocial Cancer Interventions for Latinx Families: A Critical Review - Nicole M. Vélez Agosto; Gladys Stephanie Hernandez; Sarah Chavez Chacon; Danielle Moreno; Cecilia Montiel-Nava (Journal of Family Nursing, 2026)
Cancer creates significant distress to Latinx family dynamics. Research on family interventions has omitted critical aspects that could significantly improve mental health outcomes in this vulnerable population, including the development of interventions with a robust theoretical framework that are simultaneously culturally aligned with deeply rooted Latinx values. This critical review addressed existing psychosocial interventions for families with a cancer patient, their strengths, and limitations. It expanded on three major themes relevant to designing cancer psychosocial interventions for Latinx, while also reviewing nine intervention studies that consider system-family components in intervention design and research, two of them with the additional integration of culture. Key findings were that interventions mostly incorporate some but not all systemic components. Cultural considerations are limited but promising in strengthening interventions. The purpose is to guide the future direction of research and intervention design for family therapy interventions for cancer patients and their families.